Hubungan Stres Kerja dan Dukungan Sosial dengan Work-Life Balance pada Pekerja Industri Pakan Ternak - Putranto, Gita Mahendra (Institut Nalanda, 2026)
Work-Life Balance refers to an individual's capacity to harmonize the competing demands of professional responsibilities and personal life, a condition widely recognized as fundamental to employee welfare and organizational productivity. This balance is shaped by a constellation of factors, ranging from organizational and occupational stressors to interpersonal dynamics such as peer and supervisory support. Elevated work stress levels tend to undermine this equilibrium, whereas robust social support networks may function as a psychological buffer against adverse occupational conditions. The present study sought to examine and quantify the association between work stress, social support, and Work-Life Balance among workers employed in the animal feed manufacturing sector at PT. X, Klaten Regency. Utilizing an analytic observational framework with a cross-sectional design, the study encompassed the entire workforce of 34 employees through total sampling. Data collection relied on validated survey instruments, with statistical relationships assessed via the Spearman Correlation method. Findings revealed that most workers reported moderate work stress (41.2%), moderate social support, and moderate Work-Life Balance (38.2%). Statistically significant associations were identified between work stress (p=0.017) and social support (p<0.001) with Work-Life Balance. On the basis of these results, it is recommended that the organization proactively manage employee workload distribution, enhance the quality of workplace social support, and develop structured programs to assist employees in attaining a sustainable balance between professional and personal domains.